2007
DOI: 10.1097/01.ede.0000251167.75581.98
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Breast Cancer

Abstract: There is evidence for an inverse association between physical activity and breast cancer risk. The evidence is stronger for postmenopausal breast cancer than for premenopausal breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
316
1
14

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 447 publications
(356 citation statements)
references
References 62 publications
25
316
1
14
Order By: Relevance
“…The literature on physical activity and breast cancer risk in the general population [9] indicates a risk reduction of 25-30%, independent of BMI, with a dose-response effect (for each additional hour of activity per week the risk decreased by 6%). Stronger decreases in risk were reported for, among others, recreational activity, lifetime or later life activity, vigorous activity, among postmenopausal women, women with normal BMI, and those with hormone receptor-negative tumors [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on physical activity and breast cancer risk in the general population [9] indicates a risk reduction of 25-30%, independent of BMI, with a dose-response effect (for each additional hour of activity per week the risk decreased by 6%). Stronger decreases in risk were reported for, among others, recreational activity, lifetime or later life activity, vigorous activity, among postmenopausal women, women with normal BMI, and those with hormone receptor-negative tumors [13].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, proposed mechanisms for a protective effect from physical activity are decreased lifetime exposure to estrogens and decreased percent of visceral body fat [34][35][36]. Furthermore, in the general population, the association between physical activity and breast cancer risk is most pronounced for postmenopausal and weaker for premenopausal breast cancer [9]. However, the evidence that physical activity may protect against premenopausal breast cancer is increasing [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Also, a multitude of studies have demonstrated the positive effects of physical activity in reducing the risk of developing breast cancer. 3 It has been suggested that so-called modifiable components such as obesity and insulin resistance, which are influenced by physical activity, may also affect cancer survival. 4,5 We have previously reported in a systematic review that physical activity is associated with overall survival and breast cancer-specific survival, with postdiagnosis physical activity being most beneficial for these breast cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The idea to modify at least three of these factors, i.e. alimentation, diet habits, physical activity, struggle of obesity makes it possible to reduce the incidence of breast cancer (Monninkhof et al, 2007;Cummings et al, 2009;Khan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%